Fibrillin 2 gene knockdown inhibits invasion and migration of lung cancer cells - Hong, Qiaojun; Li, Rong; Zhang, Yiyan; Gu, Kangsheng (Cellular and Molecular Biology, 2020)
To investigate the effect of Fibrillin 2 (FBN2) expression on the invasion and migration of lung cancer cells, and the underlying mechanism. Protein and mRNA expressions of FBN2 were assayed. The relationship between FBN2 protein expression and clinical characteristics of lung cancer patients was analyzed. Correlation between FBN2 expression level and patient survival time was analyzed. Moreover, the mRNA and protein expression of FBN2 in lung cancer cells and human normal lung epithelial cells were assayed. After constructing low-expressing FBN2 cells, the cell proliferation, clone formation, migration and invasion capabilities were tested. Lung cancer cells proliferation with low FBN2 expression in nude mice was measured with a nude mouse tumorigenic experiment. The mRNA and protein expressions of FBN2 in lung cancer tissues were significantly higher than those in para-cancerous tissues (p<0.05). FBN2 protein expression was significantly correlated with TNM stage, lymph node metastasis and histological type (p<0.05). Survival time was markedly reduced in patients with high FBN2 expression (p<0.001). The expressions of FBN2 mRNA and protein were markedly higher in lung cancer cells than in human normal lung epithelial cells. The proliferation, migration and invasion of lung cancer cells were significantly inhibited by FBN2 knockdown. The FBN2 knockdown significantly inhibited the protein expressions of p-FAK, p-MEK and p-ERK. FBN2 is highly expressed in lung cancer tissues, and as an oncogene, it affects the pathogenesis of lung cancer. The knockdown of the expression of FBN2 significantly inhibits the proliferation, invasion and migration abilities of lung cancer cells.